Structure and Function of Rhizosphere Soil and Root Endophytic Microbial Communities Associated With Root Rot of Panax notoginseng - Wang, Panpan; Yang, Lifang; Sun, Jialing; Yang, Ye; Qu, Yuan; Wang, Chengxiao; Liu, Diqiu; Huang, Luqi; Cui, Xiuming; Liu, Yuan (Frontiers in Plant Science, 2022)
Panax notoginseng (Burk.) F. H. Chen is a Chinese medicinal plant of the Araliaceae family used for the treatment of cardiovascular and cerebrovascular diseases in Asia. P. notoginseng is vulnerable to root rot disease, which reduces the yield of P. notoginseng. In this study, we analyzed the rhizosphere soil and root endophyte microbial communities of P. notoginseng from different geographical locations using high-throughput sequencing. Our results revealed that the P. notoginseng rhizosphere soil microbial community was more diverse than the root endophyte community. Rhodopseudomonas, Actinoplanes, Burkholderia, and Variovorax paradoxus can help P. notoginseng resist the invasion of root rot disease. Ilyonectria mors-panacis, Pseudomonas fluorescens, and Pseudopyrenochaeta lycopersici are pathogenic bacteria of P. notoginseng. The upregulation of amino acid transport and metabolism in the soil would help to resist pathogens and improve the resistance of P. notoginseng. The ABC transporter and gene modulating resistance genes can improve the disease resistance of P. notoginseng, and the increase in the number of GTs (glycosyltransferases) and GHs (glycoside hydrolases) families may be a molecular manifestation of P. notoginseng root rot. In addition, the complete genomes of two Flavobacteriaceae species and one Bacteroides species were obtained. This study demonstrated the microbial and functional diversity in the rhizosphere and root microbial community of P. notoginseng and provided useful information for a better understanding of the microbial community in P. notoginseng root rot. Our results provide insights into the molecular mechanism underlying P. notoginseng root rot and other plant rhizosphere microbial communities.